Commerce and politics in Hume's History of England - Wei, Jia (Studies in early modern cultural, political and social history ;, 2017)
Illuminates the relationship between Hume the political thinker, Hume the historian, and Hume the political economist and highlights the social, economic and institutional changes which he wove into an innovative theory of causation.